City of incurable women - Casey, Maud (Bellevue Literary Press, 2022)
"Where are the hysterics, those magnificent women of former times?" wrote Jacques Lacan. Long history's ghosts, they have been revived at last by Maud Casey in City of Incurable Women as complex, flesh-and-blood people, dispossessed and marginalized due to their gender and class but with their own stories to tell. These linked, evocative prose portraits, accompanied by period photographs and medical documents both authentic and re-imagined, poignantly restore the humanity to the 19th century female psychiatric patients confined in Paris's Salpêtrière hospital and reduced to specimens for study by the celebrated neurologist Jean-Martin Charcot and his male students--